Potensi Model Sistem Dinamik dalam Sistem Pengelolaan Sampah Perkotaan - Mawardi Heru Prasetyo; Fitryane Lihawa; Dewi Wahyuni K. Baderan (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
System dynamic models have been recognized as an effective approach in projecting and designing sustainable urban waste management systems. This study aims to explore the potential of system dynamic modeling in urban waste management. This study uses a literature study method with a qualitative descriptive approach that refers to various relevant previous studies. The results of the literature study show that the system dynamic model is able to map the complex relationships between variables in the waste management system, such as population growth, waste production, waste processing capacity, environmental impacts, and others. In addition, the system dynamic model can project future waste management conditions and prepare the most effective policy scenarios. Through simulations of various policy scenarios, the system dynamic model can provide insight into the impact of each scenario, both in terms of technical efficiency, operational costs, and reduction of waste generation in landfills. In implementing policy scenarios, collaboration between the government, community, and stakeholders is also needed in optimizing waste management programs.